Pengaruh Rasa Percaya Terhadap Budgetary Slack - Adi, Patria Prasetio (Universitas Pendidikan Indonesia, 2021)
The aim of this study is to provide comprehensive solution to manager so that they can minimize budgetary slack through informal control. Deductive approach is use in this research. We make survey to 65 employees of Indonesian Government enterprises, who prepare and approve budgets. Quantitative data analysis is completed by simple regression in order to examine the hypotheses. The result showed that there is a negative correlation between trust and budgetary slack.